Pengembangan dan validitas Pane Afdal Psychological Condition for Domestic Violance Inventory (PAPC-DVI) - Nurmaida Pane; Afdal Afdal (Jurnal Konseling dan Pendidikan, 2020)
Cases of domestic violence increase every year where the dominant victim is a wife. Many factors cause victims to receive violence, one of which is caused by psychological conditions. This study aims to develop and validate the inventory of Psychological Conditions of Afdal Pane for Domestic Violence (PAPC-DVI). This inventory will measure assertive behavior and resilience of victims of domestic violence as psychological conditions that cause victims to accept violence. Assertive behavior will measure positive assertiveness, self-affirmation, and negative assertiveness. resilience will measure equaminity, perseverance, self-reliance, meaningfulness, and existential aloneness. This research was conducted on 90 wives who experienced violence in the city of Padang using purposive sampling techniques. Furthermore, validity was analyzed using Cronbach's alpha item analysis which showed a coefficient α> .3, and the data showed that 36 PAPC-DVI items were valid. In addition, the alpha cronbach reliability value was also used to analyze the data and the results showed that the PAPC-DVI reliability coefficient for victims of domestic violence was 0.932. The results showed that PAPC-DVI in victims of domestic violence is valid in measuring psychological conditions that cause victims to receive violence so that this inventory can help in understanding psychological conditions that cause victims to receive violence and are ready to be used by subsequent researchers.